Usage of some visual aids to activate students in physics lessons - Niaura, A. (Psichologija, 1962)
Resourceful use of visual aids in Physics lessons always actives students. Students often tend to pay little attention to the practical side of Physics, because practical and graphical surveys are rarely carried out in schools. The study analyses various forms of practical and graphical surveys, their approximation with individual works of students. The author demonstrates how students are activated by using the class blackboard, inscriptions about Physics and analogies, comparisons of individual phenomena with similar phenomena. Description of universal device designed to demonstrate the variable current, electromagnetic fluctuation and contour phenomena is presented. The study also includes the analysis of application of frontal experiment and various sets of natural parts. Descriptions of sets “Amorphous and crystal solids” and “Ways of deformation” are presented. Students work actively when turning tables are used. A description of the “structure of the atom” table is provided.